A família como raiz ética do estado em Hegel - Souza, Marcelo Igor da Silva e (2021)
The present research was conceived in a systematic and argumentative way, being primarily based on the book Principles of Philosophy of Law by Hegel, seeking to understand why the family is considered the first moment of ethics, understood in the work, as the ethical root of the state. The family was considered by the author as an institution of great relevance, being considered the foundation of the realm of institutions in the development of the idea of freedom, and, therefore, established as the concrete point of exteriorization of the individual who will need to be put to universality. In this sense, the research primarily addresses the concept of family as a condition without which the state cannot implement the idea of freedom in the ethical world. At first, the question of the Hegelian system and the place of the philosophy of law was raised, as a way of highlighting the structure of the system and the relationship between the family and the philosophy of the spirit, as well as the concept of freedom and the concept of ethics. In the second moment, the different aspects necessary for the realization of the family are explained, which are: marriage, property, children's education and dissolution for the constitution of civil society. In the third moment, the peculiarities of the Hegelian state were highlighted, establishing the relationship between the family and the state, in order to understand the importance of the family in the formation of individuals as a guarantee for the realization of the idea of freedom. Finally, the essential points of the research that served as the basis for the philosophical problematic of the family as the first institution were presented, aiming to emphasize the relevance of the Hegelian thought in contemporaneity.